Plasma CRP Level and its Association with Outcome in Patients with Severe COVID-19 Pneumonia - Dhakal, Pushpa Raj; Jaiswal, Niraj Kumar; Dahal, Manish; Karki, Manoj (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTION Corona virus disease 2019 (COVID-19) has become a global public health issue with unpredictable progression to ARDS. Therapy timing of anti-inflammatory agents and immune-suppressing medication is of utmost importance. Previous studies have consistently found elevated levels of C-Reactive Protein with disease severity. In this study, we aimed to investigate the relationship between C-Reactive Protein and severe SARS-COV-2 pneumonia. MATERIAL AND METHODS Our study included 55 patients with COVID-19, admitted in COVID Unit of Universal College of Medical Sciences Teaching Hospital (UCMS-TH), Bhairahawa, Rupendehi, Nepal from 16th June 2021 to 15th September 2021. We included COVID-19 cases confirmed by a RT-PCR test with severe pneumonia based on W.H.O criteria and those undergoing C-Reactive Protein levels. RESULTS Males (56%) were more compared to females (44%). Age group 41-60 years were likely to develop severe COVID-19 pneumonia. Cough (44%), dyspnea (42%) and fever (40%) were most common symptom. Hypertension (34%) and diabetis (24%) were common comorbidities present. Patients with severe COVID-19 pneumonia had average CRP value of 59.6 mg/l. CONCLUSION Elevated CRP level was associated with COVID-19 severity.